Suction controller for window wiping robot - Muhammad Zul Husaini, Noor Azmi (2009)
The objective of this project is to develop suction controller for small-size and light weight window wiping robot. The prototype of window washing robot already been developed. The dimensions of prototype robot are approximately 150mm x 100mm x 50mm and its weight is approximately 0.5kg. For the suction controller of this robot, 3 vacuum pump and 3 active suction cups are use. To control the suction of this robot, PIC are use to program so that the suctions will be the same at all three dc motors. The speed of de motors also can be control by using potentiometer to save the power consumption according to the angle of the window. The movements of the robot are also changed by using wheels to make it compatible with the suction controller. With the suction controller, the robot can move on the surface of the window without falling down.